2017
DOI: 10.1038/sigtrans.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of an anti-HER2 single chain antibody–DM1 conjugates for the treatment of HER2-positive cancer

Abstract: Antibody–drug conjugates (ADCs) take the advantage of monoclonal antibodies to selectively deliver highly potent cytotoxic drugs to tumor cells, which have become a powerful measure for cancer treatment in recent years. To develop a more effective therapy for human epidermal growth factor receptor 2 (HER2)-positive cancer, we explored a novel ADCs composed of anti-HER2 scFv–HSA fusion antibodies conjugates with a potent cytotoxic drug DM1. The resulting ADCs, T-SA1–DM1 and T-SA2–DM1 (drug-to-antibody ratio in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 88 publications
4
33
0
2
Order By: Relevance
“…Other works have used anti-HER2 scFv antibody for targeting breast cancer cells using the Pichia pastoris as the host for the expression of antibody fragments [38] and developing anti-HER2 scFv-HSA fusion antibodies conjugates with drug DM1 [39]. In a recent study, Alric and colleagues showed the specific binding and high affinity properties of SPIONs-Cy-PEG-scFv nanoparticles against HER2 positive breast cancer cells, leading to Alric and colleagues and suggestingsuggesting the use of this nanoparticle as an imaging agents for the diagnosis of breast tumors with HER2 overexpression [40].…”
Section: Discussionmentioning
confidence: 99%
“…Other works have used anti-HER2 scFv antibody for targeting breast cancer cells using the Pichia pastoris as the host for the expression of antibody fragments [38] and developing anti-HER2 scFv-HSA fusion antibodies conjugates with drug DM1 [39]. In a recent study, Alric and colleagues showed the specific binding and high affinity properties of SPIONs-Cy-PEG-scFv nanoparticles against HER2 positive breast cancer cells, leading to Alric and colleagues and suggestingsuggesting the use of this nanoparticle as an imaging agents for the diagnosis of breast tumors with HER2 overexpression [40].…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of ADC structure was analyzed using SDS-PAGE. The average drug-antibody ratio (DAR) was calculated using the following equation [ 21 , 22 ]: Where R = A 248 /A 280 = Absorbance ratio. ε mAb 248/252 = 9.41×10 4 M -1 cm -1 , ε mAb 280 = 2.34×10 5 M -1 cm -1 , ε MMAE 248 = 1.5×10 3 M -1 cm -1 , ε MMAE 280 = 1.59×10 4 M -1 cm -1 , ε DM1 252 = 2.64×10 5 M -1 cm -1 , ε DM1 280 = 5.23×10 3 M -1 cm -1 .…”
Section: Methodsmentioning
confidence: 99%
“…[59] The anti-HER2 scFv-HSA fusion Abs showed stronga nd rapid tumor tissue penetrability and distribution compared with that of trastuzumab. [59]…”
Section: Peptide/protein Drug-albumin Fusion Proteinmentioning
confidence: 98%
“…Other important applications include Ab fragments (e.g.,F v and Fab) and albuminf usion proteins to extend the half-life in vivo. [59] For example, compared with af ull-length Ab, scFv is smaller in size, but with similar binding activity,b etter tissue penetrability,a nd lower immunogenicity;h owever,t he drawback is its short half-life in circulation. [59] The anti-HER2 scFv-HSA fusion Abs showed stronga nd rapid tumor tissue penetrability and distribution compared with that of trastuzumab.…”
Section: Peptide/protein Drug-albumin Fusion Proteinmentioning
confidence: 99%